Preparation method of anti-static ABS (Acrylonitrile Butadiene Styrene) modified plastic

By using nanostructured polyaniline in ABS resin for in situ polymerization, combined with twin-screw extruder and annealing treatment, the shortcomings in the existing anti-static ABS modified plastics in terms of performance and durability are solved, and high-performance anti-static, good mechanical properties and stability are achieved.

CN119529467AInactive Publication Date: 2025-02-28GUANGDONG JUXIONG PLASTIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411699095.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing anti-static ABS modified plastics have shortcomings in high-performance anti-static, good mechanical properties, stable and durable properties and reliable use under different environmental conditions, and it is difficult to meet multiple requirements at the same time.

Method used

ABS resin with specific molecular weight and particle size is used to recombine nanostructured polyaniline treated with surfactant, and polyaniline/ABS composite cores are formed on the surface of the ABS resin through in-situ polymerization technology. Combined with the optimization parameters and annealing treatment of the twin screw extruder, ensure that each component is evenly dispersed in the ABS matrix to form a stable anti-static ABS modified plastic.

Benefits of technology

It achieves excellent anti-static performance, good mechanical performance and stable quality, and can maintain reliable performance under different environmental conditions to meet the needs of the electrostatic sensitive field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529467A_ABST
    Figure CN119529467A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of anti-static ABS (acrylonitrile-butadiene-styrene) modified plastics, and belongs to the technical field of preparation of ABS modified plastics. The method comprises the following steps: firstly, preparing ABS resin, nano-structure polyaniline, potassium iodide, maleic anhydride grafted ABS, polyethylene glycol fatty acid ester, dioctyl phthalate and zinc stearate in a specific proportion in the aspect of raw materials; nano-structure polyaniline is subjected to special treatment and forms a composite core on part of ABS resin through in-situ polymerization, and other raw materials are preliminarily mixed. Then the materials are mixed in a double-screw extruder, parameters such as the length-diameter ratio, the rotating speed, the temperature and the feeding speed of screws are accurately set, and a screw cylinder and the screws are specially designed; the melt is formed through a mold, a product is subjected to annealing treatment, and annealing parameters comprise fine control of temperature, time, air velocity and the like. The modified plastic prepared by the method has excellent anti-static performance, keeps good mechanical performance, good low-temperature impact performance and stable durability, and can meet the requirements of various fields on anti-static materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ABS modified plastic preparation, and in particular to a method for preparing antistatic ABS modified plastic. Background Art

[0002] With the rapid development of modern industry, antistatic materials are increasingly used in many fields, especially in the fields of electronics and electrical, semiconductor manufacturing, medical equipment, and storage of flammable and explosive goods. These fields have strict requirements on the antistatic properties of materials to prevent electrostatic discharge caused by static electricity accumulation, and avoid damage to precision electronic components, fire or explosion and other serious consequences.

[0003] ABS plastic is widely used in industrial production because of its good comprehensive properties, such as hardness, toughness, glossiness, etc. However, ordinary ABS plastic itself does not have anti-static ability, and its use in static-sensitive environments is greatly limited.

[0004] At present, there are many methods for preparing antistatic ABS modified plastics. Some methods are to add traditional conductive fillers, such as carbon black, etc., but this method often affects the original mechanical properties and appearance quality of the material, and the dispersion of carbon black is poor and it is easy to agglomerate, resulting in unstable antistatic performance. Some other methods use surface coating of antistatic agents, but the antistatic effect of the materials prepared in this way is poor in durability, and the antistatic coating is easy to wear or fall off during use. In addition, some existing preparation processes, during the mixing and molding process, due to the inaccurate control of parameters such as temperature and pressure, the internal structure of the material is uneven, which affects the comprehensive performance of antistatic performance and other physical properties.

[0005] In addition, in some special environments, such as low temperature environments, the impact resistance of existing anti-static ABS modified plastics will be greatly reduced, limiting its application under a wider range of temperature conditions. Moreover, during long-term use, the anti-static performance of many anti-static ABS modified plastics will gradually decay, and cannot meet the needs of long-term stable use.

[0006] In summary, the existing antistatic ABS modified plastic preparation technology still has many shortcomings, and it is difficult to simultaneously meet the requirements of high-performance antistatic, good mechanical properties, stable durability, and reliable use under different environmental conditions. Therefore, it is necessary to develop a new preparation method for antistatic ABS modified plastics. Summary of the invention

[0007] The main purpose of the present invention is to provide a method for preparing an antistatic ABS modified plastic, which can effectively solve the problems mentioned in the background technology.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing an antistatic ABS modified plastic comprises the following steps:

[0010] S1. Raw material preparation:

[0011] Prepare ABS resin with a weight ratio of 65% to 72%, wherein the ABS resin has a narrow molecular weight distribution and a rubber phase particle size of 0.2-0.4 μm;

[0012] Prepare 12% to 18% by weight of nanostructured polyaniline (PANI), wherein the nanostructured polyaniline has a particle size of 50-150 nm and is surface-modified with sodium dodecylbenzene sulfonate;

[0013] Prepare 3% to 6% by weight of potassium iodide (KI), wherein the potassium iodide is of analytical grade and has a particle size of less than 100 μm;

[0014] Prepare 5% to 8% by weight of maleic anhydride grafted ABS (ABS-g-MAH) as a compatibilizer;

[0015] Prepare 2% to 4% by weight of polyethylene glycol fatty acid ester (PEG-400 monostearate) as an antistatic agent;

[0016] Prepare 1% to 3% by weight of a plasticizer, dioctyl phthalate (DOP);

[0017] Prepare 0.5% to 1.5% by weight of heat stabilizer zinc stearate;

[0018] S2. In-situ polymerization and compounding of polyaniline:

[0019] S2.1. Add ABS resin particles accounting for 30% of the total ABS amount and nanostructured polyaniline treated with a surfactant into a reaction kettle, and add initiator ammonium persulfate and dopant hydrochloric acid at the same time. The amount of initiator is 1% to 2% of the mass of polyaniline, the concentration of hydrochloric acid is 1-2 mol / L, and the molar ratio of hydrochloric acid to polyaniline is 1:1-1:1.2. React at 0-5°C for 2-3 hours to form a polyaniline / ABS composite core;

[0020] S2.2, add the remaining ABS resin, potassium iodide, maleic anhydride grafted ABS, polyethylene glycol fatty acid ester, dioctyl phthalate and zinc stearate into a high-speed mixer, and mix at a speed of 500-800 rpm for 10-15 minutes;

[0021] S3, Twin-screw extrusion blending

[0022] Add the above preliminary mixed material and the material containing the polyaniline / ABS composite core into a twin-screw extruder, wherein the screw aspect ratio of the twin-screw extruder is 40-48, the screw speed is set to 250-350rpm, and the temperature of each zone of the extruder is set as follows: zone 1 170-180°C, zone 2 185-195°C, zone 3 200-210°C, zone 4 215-225°C, zone 5 230-240°C, and die head temperature 240-250°C, so that each component is evenly dispersed in the ABS matrix to form a stable antistatic ABS modified plastic melt;

[0023] S4, molding and post-processing:

[0024] S4.1, forming the melt extruded by the extruder through a specific die;

[0025] S4.2. Anneal the formed product at 80-100°C for 2-4 hours.

[0026] Preferably, the nanostructured polyaniline grows on the surface of the ABS resin by in-situ polymerization to form a composite core, the stirring speed of the reactor is 100-200 rpm, and the reaction is carried out under nitrogen protection with a nitrogen flow rate of 10-20 L / h to ensure reaction uniformity and prevent oxidation.

[0027] Preferably, the maleic anhydride grafted ABS is used as a compatibilizer, with a grafting rate of 0.5% to 2% and a molecular weight of 50,000 to 100,000, for improving the compatibility between nanostructured polyaniline and ABS resin.

[0028] Preferably, the polyethylene glycol fatty acid ester forms a conductive layer on the surface of the material to enhance the antistatic effect, has a hydroxyl value of 25-60 mgKOH / g, an iodine value of less than 2gI2 / 100g, and is preheated at 40-60°C for 10-15 minutes before use.

[0029] Preferably, the feeding speed of the twin-screw extruder is 10-20kg / h, a pressure sensor is installed at the head, the pressure range is controlled at 10-20MPa, the barrel adopts a combined cooling method of water cooling and oil cooling and the inner wall is provided with a ceramic coating, the screw is made of wear-resistant and corrosion-resistant alloy material, a pressure balancing device is provided between each zone, and the screw speed is adjusted within the range of 250-350rpm to ensure that each component is fully mixed and plasticized, and to maintain stable material properties and stable extrusion process.

[0030] Preferably, the annealing treatment is carried out in an air circulating oven with an air flow rate of 0.5-1m / s. The annealing time and temperature are adjusted according to the thickness of the product and the ambient temperature of use. During the annealing process, the humidity around the product is controlled at 40% to 60%. The products are evenly spaced with an adjacent spacing of 5-10cm. The annealed products can be cooled by a combination of natural cooling and forced air cooling at an air cooling rate of 1-2m / s to eliminate residual stress and stabilize material properties.

[0031] Preferably, the potassium iodide is used after being subjected to ultrasonic dispersion treatment (ultrasonic power 200-300W, time 10-20 minutes), and its purity is not less than 99%.

[0032] Preferably, the plasticizer dioctyl phthalate is filtered through a 200-300 mesh filter before use, and the acid value is less than 0.1 mgKOH / g.

[0033] Preferably, the heat stabilizer zinc stearate is a powder with a particle size of 1-5 μm, and is activated with stearic acid (in an amount of 5% to 10% of the weight of zinc stearate) at 120-150° C. for 30-60 minutes before use.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] In terms of raw materials, the present invention selects and accurately proportions a variety of high-performance raw materials, such as ABS resin with a specific molecular weight and particle size and specially treated nanostructured polyaniline, and the raw materials work together. In terms of preparation technology, in-situ polymerization technology allows polyaniline to form a composite core on the surface of ABS resin, which improves dispersibility and antistatic properties, and the reaction conditions are precisely controlled; the parameters of the twin-screw extruder are optimized, including feeding speed, pressure control, cooling method, screw material, etc., to ensure sufficient mixing, plasticization and stable production. These advantages enable the material to have excellent antistatic properties, which can meet the needs of electrostatically sensitive fields, while maintaining good mechanical properties, good low-temperature impact performance, and excellent stability and durability. It has reliable long-term performance and a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The figure is a schematic flow chart of the method steps of the present invention. DETAILED DESCRIPTION

[0037] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0038] like Figure 1As shown, a preparation method of antistatic ABS modified plastic mainly includes four steps: raw material preparation, in-situ polymerization and compounding of polyaniline, twin-screw extrusion blending, molding and post-processing.

[0039] The present invention is described in detail below with an actual method flow example:

[0040] Raw material preparation

[0041] Selection and pretreatment of ABS resin

[0042] The ABS resin of model HI-121H produced by LG Chemical Company was selected, which has a narrow molecular weight distribution and a rubber phase particle size of about 0.3μm. Before use, the ABS resin particles were placed in a blast drying oven and dried at 70°C for 5 hours to ensure that the water content was less than 0.1%. This is because the presence of moisture will produce water vapor during the subsequent processing, affecting the performance and processing stability of the material, and may cause problems such as bubbles and surface defects in the material. This time, 68% (weight ratio) of this ABS resin was prepared.

[0043] Preparation of nanostructured polyaniline (PANI)

[0044] Nanostructured polyaniline is prepared by emulsion polymerization. Aniline is used as a monomer and hexadecyltrimethylammonium bromide is used as an emulsifier (the dosage is 8% of the weight of the aniline monomer) to initiate polymerization in the reaction system. The particle size of the obtained nanostructured polyaniline is about 100nm. Then, sodium dodecylbenzene sulfonate is used to modify its surface at a temperature of 50°C and a modification time of 2.5 hours. The dosage of sodium dodecylbenzene sulfonate is 10% of the weight of the nanostructured polyaniline. After this modification, the dispersibility of the nanostructured polyaniline in the ABS matrix can be improved. 15% (by weight) of this nanostructured polyaniline is prepared for this embodiment.

[0045] Preparation of Potassium Iodide (KI)

[0046] Select analytical grade potassium iodide, whose particle size is about 80 μm and purity is 99.5%. Before use, place potassium iodide in an ultrasonic dispersion device and ultrasonically disperse it for 15 minutes under the condition that the ultrasonic power is 250W. This is because ultrasonic dispersion can break the agglomeration of potassium iodide particles, so that it can be more evenly distributed in the material in the subsequent mixing process. The addition amount of potassium iodide in this embodiment is 5% (weight ratio).

[0047] Preparation of Compatibilizer-Maleic Anhydride Grafted ABS (ABS-g-MAH)

[0048] Maleic anhydride grafted ABS with a grafting rate of 1% and a molecular weight of about 80,000 is selected as a compatibilizer. Its function is to improve the compatibility between nanostructured polyaniline and ABS resin. Prepare 6% (weight ratio) maleic anhydride grafted ABS.

[0049] Preparation of antistatic agent - polyethylene glycol fatty acid ester (PEG-400 monostearate)

[0050] A polyethylene glycol fatty acid ester having a hydroxyl value of 40 mgKOH / g and an iodine value of less than 2 gI2 / 100 g is selected. Before being added to the high-speed mixer, it is preheated at 50° C. for 12 minutes to improve its fluidity in the mixed system, thereby better forming a conductive layer on the surface of the material and enhancing the antistatic effect. In this embodiment, the addition amount is 3% (by weight).

[0051] Preparation of plasticizer-dioctyl phthalate (DOP)

[0052] Dioctyl phthalate with an acid value of less than 0.1 mgKOH / g was used as a plasticizer. Before use, it was filtered through a 250-mesh filter to remove possible impurities and ensure the quality of the material. In this embodiment, the amount of DOP added was 2% (by weight).

[0053] Preparation of heat stabilizer-zinc stearate

[0054] Select zinc stearate powder with a particle size of about 3 μm. Perform activation treatment before use, using stearic acid as an activator, the amount of stearic acid used is 8% of the weight of zinc stearate, and activate at 130° C. for 45 minutes. This can improve the thermal stability of zinc stearate. The addition amount of zinc stearate in this embodiment is 1% (weight ratio).

[0055] In-situ polymerization and compounding of polyaniline

[0056] In-situ Polymerization of Polyaniline on ABS Resin Surface

[0057] In a 5L stainless steel reactor with a stirrer, a thermometer and a condenser (the inner wall of the reactor is smooth, which can reduce the adsorption of materials and the introduction of impurities during the reaction process), add dried ABS resin particles accounting for 30% of the total ABS (i.e. 20.4kg, calculated based on the total ABS amount of 68kg) and nanostructured polyaniline treated with a surfactant. At the same time, add initiator ammonium persulfate (ammonium persulfate is prepared into an aqueous solution with a concentration of 0.8mol / L before use, and is prepared and used immediately), the initiator dosage is 1.5% of the mass of polyaniline, and dopant hydrochloric acid (hydrochloric acid concentration is 1.5mol / L, and the molar ratio of hydrochloric acid to polyaniline is 1:1.1). The stirring blade of the reactor adopts an inclined design with an inclination angle of 45° and a stirring speed of 150rpm. React at 3°C ​​for 2.5 hours. During the reaction process, the reaction system is protected by nitrogen with a nitrogen flow rate of 15L / h. Nitrogen protection can prevent oxidation reaction from affecting the polymerization effect, ensuring the in-situ polymerization growth of polyaniline on the surface of ABS resin to form a high-quality polyaniline / ABS composite core.

[0058] Preliminary mixing of the remaining raw materials

[0059] The remaining 47.6 kg ABS resin, 3.4 kg potassium iodide, 5.44 kg maleic anhydride grafted ABS, 2.04 kg polyethylene glycol fatty acid ester, 1.36 kg dioctyl phthalate and 0.68 kg zinc stearate are added to the high-speed mixer. The speed of the high-speed mixer is set to 650 rpm and the mixing time is 12 minutes. During this process, each component can be added in batches, with an interval of 1.5 minutes between each addition to ensure more uniform mixing. At the same time, 0.2% (weight ratio, i.e. 0.2 kg) of dispersing aid ethylene bis stearamide can be added to further improve the dispersing effect of each component.

[0060] Twin screw extrusion compounding

[0061] Materials added to twin screw extruder

[0062] The above preliminary mixed material and the material containing the polyaniline / ABS composite core are added to the twin-screw extruder. The twin-screw extruder has a screw length-diameter ratio of 45, a screw speed set at 300rpm, and a feed rate of 15kg / h. The barrel of the twin-screw extruder adopts a cooling method combining water cooling and oil cooling, with a water cooling temperature of 20°C and an oil cooling temperature of 100°C. This cooling method can accurately control the temperature of each zone. The inner wall of the barrel is provided with a ceramic coating to improve wear resistance and corrosion resistance. The screw is made of wear-resistant and corrosion-resistant alloy materials (such as Hastelloy C-276) to extend the service life of the screw. The screw elements include conveying elements, kneading elements and mixing elements, and the arrangement order is: conveying element-kneading element-conveying element-mixing element-conveying element, and the quantity ratio is 3:2:3:2:3. This arrangement and quantity are optimized according to the characteristics of the material to achieve the best mixing effect. A pressure balance device is installed between each zone of the twin-screw extruder to ensure smooth transition and uniform distribution of materials between zones. A pressure sensor is installed at the die head to monitor pressure changes in real time and the pressure is controlled at 15MPa.

[0063] Temperature setting and mixing

[0064] The temperature of each zone of the extruder is set as follows: Zone 1 175℃, Zone 2 190℃, Zone 3 205℃, Zone 4 220℃, Zone 5 235℃, and die head temperature 245℃. The material is fully sheared, mixed and plasticized in the extruder, so that each component is evenly dispersed in the ABS matrix to form a stable anti-static ABS modified plastic melt. In this process, the screw speed of the twin-screw extruder can be fine-tuned within the range of 290-310rpm according to the actual extrusion situation of the material to ensure uniform mixing and stable extrusion of the material.

[0065] Forming and post-processing

[0066] forming

[0067] The melt extruded from the extruder is molded through an injection mold to obtain the required plastic product sample. For injection molding, the injection pressure is 80MPa and the holding time is 8s. The surface of the mold cavity is polished, and the surface roughness Ra value is less than 0.1μm to improve the appearance quality and demolding performance of the product. The gate design of the mold is optimized according to the shape and size of the product, and the gate diameter is 3mm to ensure the filling effect of the material. The cooling system of the mold uses circulating water with adjustable water temperature, and the water temperature is adjusted to 15℃ to ensure the rapid cooling and molding quality of the product. At the same time, an exhaust groove is set in the mold with a depth of 0.03mm, which can effectively discharge the gas in the mold cavity and further ensure the quality of the product.

[0068] Post-treatment-annealing

[0069] The formed products are annealed at 90°C in an air-circulating oven with an air flow rate of 0.8m / s. The products are placed evenly at intervals during the annealing process, with a distance of 8cm between adjacent products. The annealing time is adjusted according to the thickness of the product. The thickness of the sample is 5mm and the annealing time is 3 hours. Annealing can eliminate the residual stress inside the product and further stabilize the performance of the material. During the cooling process of the annealed products, a combination of natural cooling and forced air cooling is adopted, with an air cooling speed of 1.5m / s. The annealed products are cleaned before packaging to remove surface dust and impurities. Finally, the anti-static performance of the annealed products is tested, and the surface resistance value is required to be less than 1×10 10 Ω, if not satisfied, rework is performed. Through the above steps, antistatic ABS modified plastic products with excellent antistatic performance, good mechanical properties and stable quality are successfully prepared.

[0070] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing an antistatic ABS modified plastic, characterized in that: The following steps are involved: S1. Raw material preparation: Prepare ABS resin with a weight ratio of 65% to 72%, wherein the ABS resin has a narrow molecular weight distribution and a rubber phase particle size of 0.2-0.4 μm; Prepare 12% to 18% by weight of nanostructured polyaniline, wherein the nanostructured polyaniline has a particle size of 50-150nm and is surface-modified with sodium dodecylbenzene sulfonate; Prepare 3% to 6% by weight of potassium iodide, wherein the potassium iodide is of analytical grade and has a particle size of less than 100 μm; Prepare 5% to 8% by weight of maleic anhydride grafted ABS as a compatibilizer; Prepare 2% to 4% by weight of polyethylene glycol fatty acid ester as an antistatic agent; Prepare 1% to 3% by weight of a plasticizer, dioctyl phthalate; Prepare 0.5% to 1.5% by weight of heat stabilizer zinc stearate; S2. In-situ polymerization and compounding of polyaniline: S2.

1. Add ABS resin particles accounting for 30% of the total ABS amount and nanostructured polyaniline treated with a surfactant into a reaction kettle, and add initiator ammonium persulfate and dopant hydrochloric acid at the same time. The amount of initiator is 1% to 2% of the mass of polyaniline, the concentration of hydrochloric acid is 1-2 mol / L, and the molar ratio of hydrochloric acid to polyaniline is 1:1-1:1.

2. React at 0-5°C for 2-3 hours to form a polyaniline / ABS composite core; S2.2, add the remaining ABS resin, potassium iodide, maleic anhydride grafted ABS, polyethylene glycol fatty acid ester, dioctyl phthalate and zinc stearate into a high-speed mixer, and mix at a speed of 500-800 rpm for 10-15 minutes; S3, Twin-screw extrusion blending Add the above preliminary mixed material and the material containing the polyaniline / ABS composite core into a twin-screw extruder, wherein the screw aspect ratio of the twin-screw extruder is 40-48, the screw speed is set to 250-350rpm, and the temperature of each zone of the extruder is set as follows: zone 1 170-180°C, zone 2 185-195°C, zone 3 200-210°C, zone 4 215-225°C, zone 5 230-240°C, and die head temperature 240-250°C, so that each component is evenly dispersed in the ABS matrix to form a stable antistatic ABS modified plastic melt; S4, molding and post-processing: S4.1, forming the melt extruded by the extruder through a specific die; S4.

2. Anneal the formed product at 80-100°C for 2-4 hours.

2. The method for preparing an antistatic ABS modified plastic according to claim 1, characterized in that: The nanostructured polyaniline grows on the surface of the ABS resin through in-situ polymerization to form a composite core. The stirring speed of the reactor is 100-200 rpm, and the reaction is carried out under nitrogen protection with a nitrogen flow rate of 10-20 L / h.

3. The method for preparing an antistatic ABS modified plastic according to claim 2, characterized in that: The maleic anhydride grafted ABS is used as a compatibilizer, and its grafting rate is 0.5% to 2%, and the molecular weight is 50,000 to 100,000.

4. The method for preparing an antistatic ABS modified plastic according to claim 1, characterized in that: The polyethylene glycol fatty acid ester forms a conductive layer on the surface of the material, has a hydroxyl value of 25-60 mgKOH / g, and an iodine value of less than 2 gI2 / 100 g, and is preheated at 40-60° C. for 10-15 minutes before use.

5. The method for preparing an antistatic ABS modified plastic according to claim 1, characterized in that: The feeding speed of the twin-screw extruder is 10-20kg / h, a pressure sensor is installed at the head, the pressure range is controlled at 10-20MPa, the barrel adopts a combined cooling method of water cooling and oil cooling and the inner wall is provided with a ceramic coating, the screw is made of wear-resistant and corrosion-resistant alloy material, a pressure balancing device is provided between each zone, and the screw speed is adjusted within the range of 250-350rpm.

6. The method for preparing an antistatic ABS modified plastic according to claim 1, characterized in that: The annealing treatment is carried out in an air circulating oven with an air flow rate of 0.5-1m / s. During the annealing process, the humidity around the product is controlled at 40%-60%. The products are evenly spaced with an adjacent spacing of 5-10cm. The annealed products can be cooled by a combination of natural cooling and forced air cooling, with an air cooling speed of 1-2m / s.

7. The method for preparing an antistatic ABS modified plastic according to claim 1, characterized in that: The potassium iodide is used after being subjected to ultrasonic dispersion treatment, with an ultrasonic power of 200-300W and a time of 10-20 minutes, and its purity is not less than 99%.

8. The method for preparing an antistatic ABS modified plastic according to claim 1, characterized in that: The plasticizer dioctyl phthalate is filtered through a 200-300 mesh filter before use, and the acid value is less than 0.1 mgKOH / g.

9. The method for preparing an antistatic ABS modified plastic according to claim 1, characterized in that: The heat stabilizer zinc stearate is a powder with a particle size of 1-5 μm, which is activated with stearic acid at 120-150° C. for 30-60 minutes before use, and the amount of stearic acid used is 5% to 10% of the weight of the zinc stearate.